Comparison of Efficacy and Safety of Vildagliptin and Linagliptin in Patients of Type 2 Diabetes Mellitus with Chronic Kidney Disease (Community Based Medical Journal, 2025)
Both vildagliptin and linagliptin are dipeptidyl peptidase-4 (DPP-4) inhibitors used to manage blood sugar levels in patients with type 2 diabetes mellitus (T2DM), including those with chronic kidney disease (CKD). This randomized comparative study was conducted in the Department of Medicine, Community Based Medical College, Bangladesh (CBMC,B) Hospital, Mymensingh Bangladesh, between January and December 2023, to compare the efficacy and safety of vildagliptin and linagliptin in patients of type 2 diabetes mellitus (T2DM) with chronic kidney disease (CKD). A total of 120 type 2 diabetes mellitus (T2DM) patients with chronic kidney disease (CKD) were enrolled and randomly divided into two groups. Group A (60 patients taking vildagliptin 50 mg) and Group B (60 patients taking linagliptin 5 mg). Both groups received respective medication along with metformin 500 mg and glimepiride 2 mg. Baseline demographic and diagnostic findings showed similar results between Group A and Group B. Both groups experienced significant improvements in FBG and PPG levels, along with a notable reduction in creatinine levels. LDL-C levels decreased in both groups, but the change was only statistically significant in Group B. Additionally, creatinine and AST levels significantly decreased in both groups. At follow-up, Group B had significantly lower PPG levels compared to Group A. Both vildagliptin and linagliptin are effective and safe for type 2 diabetes patients with chronic kidney disease. However, linagliptin shows some superiority over vildagliptin in controlling postprandial glucose levels.  CBMJ 2025 January: Vol. 14 No. 01 P: 96-100